PATTERNS OF URANIUM ORE METASOMATITES LOCALISATION IN ASSOCIATION WITH FEATURES OF THE UKRAINIAN SHIELD LITHOSPHERE'S DEEP STRUCTURE - Калашник, Г. (Київський національний університет імені Тараса Шевченка, 2016)
The objective of the study is to identify new patterns of formation of uranium ore metasomatic rocks due to the nature of the deep structure of lithosphere of the Ukrainian Shield. Analysis of geophysical, geological, radiogeochemical information on the specific nature of the formation, placement of the main types of uranium ore metasomatic rocks in the Ukrainian shield in close connection with the features of the deep structure of the lithosphere, asthenosphere and fault tectonics was carried out. Pre-conditions of specialized uranium ore metasomatic rocks and formation of large uranium ore concentration within these rocks due to mantle source of ore components were identified. Features of the deep structure of the lithosphere and their physical parameters that affect the conditions of intensive ore genesis in the formation of uranium deposits in the medium-temperature sodium-carbonate metasomatic and high-temperature silicon-potassium metasomatic rocks were revealed. We have obtained optimal conditions for the formation of large-scale uranium ore concentration at all stages of the ore-forming process for the Ukrainian Shield conditions, from the primary large-scale uranium ore concentration process in the asthenosphere, the specific features of ore-controlling faults trans lithospheric and / or units of their intersection to the final stage of ore deposition in metasomatites. The intensity of the uranium ore genesis in the mediumtemperature carbonate-sodium metasomatites is determined by the characteristics of the asthenospheric traps in the underlying ore region layer of the upper mantle, by the structural factors, including complications of structural elements of translithospheric faults, by their non-uniform permeability, by the kinetic energy of uprise of uranium-bearing fluid, depending on the degree of CO2 saturatio, concentration of which has played a significant role in the implementation of hydro-gas fault mechanism in structures with non-uniform permeability in the upper crust. The practical significance of this research is improving metallogenic predictions efficiency by expanding the range of criteria of the intensity of ore genesis geophysical and petrological and geochemical indicators of the primary large-scale concentration of uranium in the asthenosphere. It allows to determine the prospects of the territories as for the formation of large uranium ore concentration in metasomatic formations with the isolation of the most probable areas of their localization.

Метою проведеної роботи є виявлення нових закономірностей формування урановорудних метасоматитів у зв'язку з особливостями глибинної будови літосфери Українського щита (УЩ). Виконано аналіз геофізичної, геологічної, радіогеохімічної інформації про особливості формування, розміщення основних типів урановорудних метасоматитів на УЩ в тісному зв'язку з особливостями глибинної будови літосфери, астеносфери, розломною тектонікою. Визначено передумови виникнення спеціалізованих урановорудних метасоматитів і формування в них значних за запасами рудоконцентрацій урану за рахунок мантійних джерел рудогенних компонентів. Виявлено особливості глибинної будови літосфери та її фізичні параметри, які впливали на умови інтенсивного рудогенезу при формуванні родовищ урану в середньотемпературних карбонатно-натрієвих і високотемпературних кремній-калієвих метасоматитах. Виділено оптимальні умови формування масштабних рудоконцентрацій урану на всіх стадіях рудоутворюючого процесу для умов УЩ, від процесу первинної масштабної рудоконцентрації урану в астеносфері, специфічних особливостей рудоконтролюючих розломів транслітосферного проникнення та/або вузлів їх перетину і фінальної стадії рудовідкладення в метасоматитах. Встановлено, що інтенсивність уранового рудогенезу в середньотемпературних карбонатно-натрієвих метасоматитах визначається характеристиками астеносферної пастки в підстилаючому рудний район шарі верхньої мантії, структурними чинниками, зокрема ускладненнями структурних елементів транслітосферних розломів, неоднорідною їхньою проникністю, кінетичною енергією підйому ураноносного флюїду, що залежить від ступеня його насиченості СО2, концентрація якого відігравала значну роль у здійсненні механізму гідрогазорозриву в розломних структурах з неоднорідною проникністю у верхніх структурних горизонтах земної кори. Практичне значення проведеного дослідження полягає у підвищенні ефективності металогенічних прогнозів за рахунок розширення спектру критеріїв інтенсивності рудогенезу із залученням геофізичних і петролого-геохімічних індикаторів можливості первинного масштабного концентрування урану в астеносфері. Це дозволяє обґрунтовано визначати перспективи територій на можливість формування значних за запасами рудоконцентрацій урану в метасоматичних формаціях з виділенням площ найбільш вірогідної їх локалізації.
ЗАКОНОМІРНОСТІ ФОРМУВАННЯ УРАНОВОРУДНИХ МЕТАСОМАТИТІВ У ЗВ'ЯЗКУ З ОСОБЛИВОСТЯМИ ГЛИБИННОЇ БУДОВИ ЛІТОСФЕРИ УКРАЇНСЬКОГО ЩИТА
Keywords: uranium ore metasomatic; lithosphere; mantle ore components; Ukrainian Shield; урановорудні метасоматити; літосфера; мантійні рудні компоненти; Український щит